Enantiopurity and absolute configuration determination of arene cis‐dihydrodiol metabolites and derivatives using chiral boronic acids. Issue 1 (11th October 2017) - Boyd, Derek R.; Sharma, Narain D.; Goodrich, Peter A.; Malone, John F.; McConville, Gareth; Harrison, John S.; Stevenson, Paul J.; Allen, Christopher C.R.
Abstract: The relative merits of the methods employed to determine enantiomeric excess ( ee ) values and absolute configurations of chiral arene and alkene cis ‐1, 2‐diol metabolites, including boronate formation, using racemic or enantiopure (+) and (−)‐2‐(1‐methoxyethyl)phenylboronic acid (MEPBA), are discussed. Further applications of: 1) MEPBA derived boronates of chiral mono‐ and poly‐cyclic arene cis ‐dihydrodiol, cyclohex‐2‐en‐1‐one cis ‐diol, heteroarene cis / trans ‐2, 3‐diol, and catechol metabolites in estimating their ee values, and 2) new chiral phenylboronic acids, 2‐[1‐methoxy‐2, 2‐dimethylpropyl]phenyl boronic acid (MDPBA) and 2‐[1‐methoxy‐1‐phenylmethyl]phenyl boronic acid (MPPBA) and their advantages over MEPBA, as reagents for stereochemical analysis of arene and alkene cis ‐diol metabolites, are presented. Abstract :